Investigating EFL Teaching Strategies in Motivating Students in Learning English Vocabulary - Ervina Azisa Azisa; Sahril; Abdullah (Program Studi Magister Pendidikan Bahasa Inggris, Fakultas Bahasa dan Sastra- Universitas Negeri Makassar., 2025)
This research aims to explore and identify the teaching strategies used by an English teacher to motivate students in learning English vocabulary. The subject of this study is an English teacher at SMPN 51 Makassar, and the research employs a descriptive qualitative method to provide a deeper understanding of the teacher's practices and their impact on students’ motivation. The data for this study were collected through a combination of classroom observations, interviews with the teacher, and documentation of teaching materials and student work. The data obtained was analyzed using four stages: data collection, data condensation, data display, and drawing conclusion. The results of the study indicate that the teacher uses a variety of motivational strategies to foster a positive and engaging learning environment. These strategies include building strong, positive relationships with students, which promotes trust and a sense of security in the classroom. Additionally, the teacher creates a fun and supportive atmosphere that encourages student participation and engagement. The teacher also employs techniques to arouse students' interest in learning new vocabulary, such as connecting the material to real-life experiences and students’ personal interests. Furthermore, the teacher works to maintain students' enthusiasm for learning by offering varied teaching methods and regularly incorporating interactive activities that sustain interest throughout lessons. Another key finding from the research is the teacher’s emphasis on providing constructive feedback to students. This feedback plays a vital role in reinforcing students’ understanding and boosting their self-confidence, which in turn contributes to their ongoing motivation. By recognizing students’ efforts and providing guidance for improvement, the teacher helps cultivate a growth mindset, where students feel empowered to continue learning and improving.